If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5a + b = 2 Solving 5a + b = 2 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-1b' to each side of the equation. 5a + b + -1b = 2 + -1b Combine like terms: b + -1b = 0 5a + 0 = 2 + -1b 5a = 2 + -1b Divide each side by '5'. a = 0.4 + -0.2b Simplifying a = 0.4 + -0.2b
| (5.6*10^-6)/(7*10^3)= | | -7x-4(5x-2)=197 | | 3x-3(x+1)=e | | 5.6*10^-6/7*10^3= | | 14x-17=6x-10 | | 5.6X10^-6/7X10^3= | | h^2+9h+8=0 | | sin^2xcos^2x=1-cos4x/8 | | 5(a-2)=3(a+1) | | 4y-25=35 | | 2mi=ft | | -2x+7y+-7y=0+-7y | | 4x-16=10x+8 | | 25-(-p+18)=45 | | 120=5x+5(-3x+10) | | 360-59-90-19x= | | 1 = z4– 3 | | h^2-14h+24=0 | | x^2+15x-8=8 | | 2(4x+7)+x= | | 4x-14=42x | | x+16+3x=18+2y | | 8x+3y+24=0 | | fg(-1)=0 | | 15-5/12 | | 4x+56=-6x-194 | | 2p+2=8 | | -g(f)= | | d^2=0 | | 6x2/3=N | | 63+x=10x | | ln(x-4)-ln(x+5)=ln(x-6)-ln(x+6) |